Addressing Climate Change at the Community Level in the United States - Lachapelle, Paul R.; Albrecht, Don E.; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
The concept of community, in all its diverse definitions and manifestations, provides a unique approach to learn more about how groups of individuals and organizations are addressing the challenges posed by climate change. This new volume highlights specific cases of communities developing innovative approaches to climate mitigation and adaptation around the United States. Defining community more comprehensively than just spatial geography to include also communities of interest, identity and practice, this book highlights how individuals and organizations are addressing the challenges posed by climate change through more resilient social processes, government policies and sustainable practices. Through close examinations of community efforts across the United States, including agricultural stakeholder engagement and permaculture projects, coastal communities and prolonged drought areas, and university extension and local governments, this book shows the influence of building individual and institutional capacity toward addressing climate change issues at the community level. It will be useful to community development students, scholars and practitioners learning to respond to unexpected shocks and address chronic stress associated with climate change and its impacts.
Chapter 1: Community Approaches to Climate Change: Challenges and Opportunities in the 21st Century -- Paul Lachapelle and Don Albrecht -- SECTION ONE: COMMUNITIES OF INTEREST AND IDENTITY -- Chapter 2: Earth's Changing Climate: A Community Primer -- Rob Davies -- Chapter 3: Public Opinion on Climate Change in Rural America: A Potential Barrier to Resilience -- Shawn K. Olson-Hazboun and Peter D. Howe -- Chapter 4: Building Local Resilience to Climate Change through Citizen Science, Environmental Education, and Decision-making -- Erin E. Posthumus, LoriAnne Barnett, Theresa M. Crimmins, Jody Einerson, Esperanza Stancioff and Peter L. Warren -- Chapter 5: Creating a Civic Spark: Using AmeriCorps National Service to Catalyze Rural Climate Change Action -- Kif Scheuer, Kristen Wraith and Kristin Brubaker -- Chapter 6: Participatory Research to Assess the Climate Resiliency of Snow-fed River Dependent Communities: A Collaborative Modeling Case Study in the Truckee-Carson River System -- Loretta Singletary and Kelley Sterle -- Chapter 7: Nevadas Approach to Minimizing the Risk from Prolonged Drought -- Mark Walker and Kerri Jean Ormerod -- SECTION TWO: COMMUNITIES OF PRACTICE -- Chapter 8: Mitigating Projected Impacts of Climate Change and Building Resiliency through Permaculture -- Roslynn Brain McCann, Jeremy Lynch and Jeff Adams -- Chapter 9: Engaging Southeastern Science Educators in the Development of a Climate Change Instructional Module -- Martha C. Monroe and Annie Oxarart -- Chapter 10: Engaging with Michigan Agricultural Stakeholders to Address Climate Change -- Julie E. Doll and Claire Needham Bode -- Chapter 11: Communicating Climate Change at the Community Level -- Huston Gibson -- Chapter 12: University Extension Communities of Practice: Learning, Communicating, and Engaging on Climate Change Adaptation and Mitigation in the United States Corn Belt -- Gabrielle Roesch-McNally, J. Arbuckle, Jamie Benning, Lois Wright Morton and Adam Wilke -- SECTION THREE: COMMUNITIES OF PLACE -- Chapter 13: Variables Influencing the Adoption of Sustainability Programs by Local Governments -- John J. Duffy and Susan Todd -- Chapter 14: Supporting Climate Adaptation Planning in Northwest Alaska -- Nathan P. Kettle, Josephine-Mary Sam, Sarah F. Trainor and Glenn T. Gray -- Chapter 15: Financial Resilience of Local Government Impacted by Natural Disasters: A Framework for Calculating Climate Change Risk Liability -- J. Matthew Fannin -- Chapter 16: The Role of Community Capitals in Climate Change Adaptation in Binational Setting -- Kristen A. Goodrich, Danielle Boudreau, Jeffrey A. Crooks, Ana Eguiarte and Julio Lorda -- Chapter 17: Engaging Citizens to Address Community Climate Change Issues -- Daniel Kahl and Amber Campbell -- Chapter 18 : Local Adaptation to Climate Change: What Comes Next? -- Don Albrecht and Paul Lachapelle.
Includes bibliographical references and index.
Also available in print format.
Keywords: Climatic changes -- Social aspects -- United States; Climate change mitigation -- Social aspects -- United States; Rural development -- Environmental aspects -- United States; Asset-based community development; Bottom-up community infrastructure; Community action; Community Built Association; Community engagement; Community involvement; Downtown revitalization; Do-it-yourself urbanism; Empowerment; Local capacity; Local culture; Local identity; Public engagement; Right to the city; Electronic books